2013
DOI: 10.1007/s11746-013-2208-1
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Thermal Profile of Structured Lipids Produced by Continuous Enzymatic Interesterification

Abstract: Enzymatic interesterification has been shown to be an alternative for the production of structured lipids resembling human milk fat. The knowledge of the physical properties of fat is an important tool for the implementation of this fat in a food matrix. The enzymatic interesterification reaction modifies the composition of triacylglycerols changing the crystallization properties and polymorphic form of fats. Blends containing different proportions of lard and soybean oil (80:20, 70:30, 40:60, 30:70 and 20:80)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…RSO presented a broad exothermic peak I with the lowest crystallization onset temperature of −8.8°C (Table ). This could be explained by the crystallization of triunsaturated TAGs in RSO, which was in accordance to the thermal phenomenon of RSO as reported in the previous study . As compared to RSO, the blend of RSO and DSM exhibited three exothermic peaks, in which two more sharp peaks (peak II and III) demonstrated an evident tendency toward higher temperatures due to the incorporation with DSM.…”
Section: Resultssupporting
confidence: 89%
“…RSO presented a broad exothermic peak I with the lowest crystallization onset temperature of −8.8°C (Table ). This could be explained by the crystallization of triunsaturated TAGs in RSO, which was in accordance to the thermal phenomenon of RSO as reported in the previous study . As compared to RSO, the blend of RSO and DSM exhibited three exothermic peaks, in which two more sharp peaks (peak II and III) demonstrated an evident tendency toward higher temperatures due to the incorporation with DSM.…”
Section: Resultssupporting
confidence: 89%
“…A higher degree of saturation has been correlated with a higher SFC and hardness of lard in other studies (Campos et al 2002;Gläser et al 2004). The peak temperature (Table 1) was also obtained from the DSC melting curves and denotes the temperature at which the greatest proportion of lipids melt with the maximum thermal effect (da Silva et al 2013). The melting peak temperature of lard from the S pork back fat was higher than that of the U pork back fat.…”
Section: Pork Back Fats Characteristicsmentioning
confidence: 85%
“…The results indicated that the predominant crystal form had changed from β to β . The changes in crystal form were probably due to the changes in fatty acid composition within TAGs under the catalytic action of Lipozyme RM IM 33,34 . Type β crystals were small and have a morphology suited to the plasticity characteristics desirable for margarine stock.…”
Section: Polymorphism By X-ray Diffraction Spectroscopymentioning
confidence: 99%